2022
DOI: 10.1186/s12872-022-02948-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum C-reactive protein and senile hypertension

Abstract: Background Hypertension has become an important health risk factor in the twenty-first century, especially for the elderly. Studies have confirmed that inflammation is involved in the development of hypertension and that the inflammatory marker C-reactive protein(CRP) is significantly associated with hypertension. Therefore, in this study, we aimed to explore the CRP correlation with hypertension in the elderly. Methods Serum CRP levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…The BMI of the participants was 23.3 kg/m 2 , similar to that reported by Seo et al [24], who examined the impact of BMI on the physical fitness of the elderly in South Korea, and by He et al [25], who investigated the relationship between serum CRP levels and senile hypertension. Impairments to ADL, which reflect the physical health status of the elderly, tend to increase with age, indicating a decline in physical function with aging [26].…”
Section: Discussionsupporting
confidence: 69%
“…The BMI of the participants was 23.3 kg/m 2 , similar to that reported by Seo et al [24], who examined the impact of BMI on the physical fitness of the elderly in South Korea, and by He et al [25], who investigated the relationship between serum CRP levels and senile hypertension. Impairments to ADL, which reflect the physical health status of the elderly, tend to increase with age, indicating a decline in physical function with aging [26].…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have shown a positive correlation between CRP and hypertension (Table 2). For instance, a study of 196 hypertensive patients over the age of 65 found that the increase in CRP was positively correlated with hypertension in the elderly, though not with the severity of hypertension [17]. Another randomized clinical trial [18] of 243 patients over 24 months found that high levels of C-reactive protein, measured using a high-sensitivity CRP (hs-CRP) assay, were related to HMOD, and hypertensive patients with combined organ damage had higher hs-CRP than hypertensive patients without organ damage.…”
Section: C-reactive Proteinmentioning
confidence: 99%